Interdisciplinary Collaboration in Social Work Management: Models, Barriers, and Strategies for Integrated Sustainable Service Delivery - Durmus Senyapar, Hafize Nurgul (Technium Social Sciences Journal, 2025)
Interdisciplinary collaboration has become a strategic imperative in social work management, where complex social challenges such as poverty, homelessness, chronic illness, and family violence exceed the capacity of single-sector responses. This study aims to evaluate the impact of interdisciplinary partnerships among social work, healthcare, and public administration on more integrated, equitable, and client-centered service delivery. Adopting a qualitative exploratory design based on a structured literature review, the research synthesizes peer-reviewed studies, case analyses, and policy reports published between 2000 and 2025. The findings reveal that integrated service delivery, co-located service hubs, collaborative case management, and technology-enabled systems reduce service fragmentation and improve continuity of care. However, significant barriers—including communication breakdowns, organizational silos, conflicting professional values, fragmented funding, and legal and ethical restrictions—undermine effective collaboration. Strategies to strengthen interdisciplinary practice include implementing standardized communication protocols, promoting interprofessional education, establishing supportive policy frameworks, utilizing digital platforms, and fostering transformational leadership. These strategies are interdependent and require systemic alignment to succeed. The study offers practical implications for policymakers, managers, and practitioners by providing a roadmap for institutionalizing collaboration and aligning practices with the United Nations’ Sustainable Development Goals, particularly those related to health, reducing inequalities, and strengthening institutions (SDG 3, SDG 10, SDG 16). Ultimately, interdisciplinary collaboration emerges not only as a professional necessity but also as a global priority for sustainable and inclusive social service delivery.